The Role of Self Leadership for College Students in Starting a Business: A Phenomenological Approach of Start Up in Jakarta - Baby SM Poernomo; Jana Sandra; Ade Suryana; Sunarmin Sunarmin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research is aimed at answering the question of how to apply student self-leadership in managing start-ups and what efforts are made by universities to improve student self-leadership so that they can lead their start-up businesses to progress and develop. This is a qualitative research with a phenomenological approach. Data collection is done through unstructured interviews and in a fluid atmosphere. This type of interview is an effort to find problems more openly where the parties involved are invited to ask for opinions and express their opinions, ideas in depth. In this study, interviews were conducted with 20 students who run start-ups in Jakarta. This research shows that self-leafdership is very much needed for those who are building startup businesses, especially students. By understanding self leadership, students can motivate themselves to always think constructively and leave destructive thoughts behind. With self-leadership, students can also correct mistakes they have made and at the same time find solutions for future improvements. This study proves that self leadership strategies consisting of behavior focused, natural rewards and constructive though patterns are important aspects that support student success in building startup businesses.